Exploring factors associated with company employee involvement in physical activities with older psychiatric outpatients: a qualitative study - van Kraanen, Kristel; Smit, Jakobus; Sassen, Barbara; Deenik, Jeroen; de Kruif, Anja; Rijks, Stella; de Kock, Annemiek; Rhebergen, Didi (Frontiers in Psychiatry, 2026)
BackgroundWith ageing societies, the number of older persons with mental health problems are increasing the coming decades. Physical health and loneliness are well known risk factors. Effective interventions, promoting social interaction, are hampered by stigma associated with mental health. This is further compounded by a global mental healthcare and demand gap, highlighting the need for volunteer-based support in addressing the needs of older mental health patients.AimThis study aims to explore factors associated with company employee participation in a walking project designed for psychiatric outpatients aged 60 and older.MethodsA qualitative design was employed. For a diverse representation of perspectives on the topic, contact was sought with HR representatives, vitality managers or directors from 250 companies (profit and nonpofit) with different ownership structures, management styles, and decision-making processes. Data were collected through semi-structured interviews and analyzed using the Constant Comparative Method with a thematic approach via Atlas.ti. Analysis occurred in six phases: data preparation, familiarization, finalization, open coding, axial coding, and selective coding.Findings13 of 250 companies engaged in interviews. Respondents viewed the project positively, but highlighted significant barriers to structural volunteer engagement, related to views on volunteerwork, preconditions, and employee-, patient-, and company-related factors. A pilot project with motivated employees is recommended by respondents, aligning initiatives with Corporate Social Responsibility (CSR) goals.ConclusionThis study highlights the complexity of company involvement within mental health care. By adressing stigma reduction and employee engagement, companies can contribute to a more inclusive and compassionate society.